PENGARUH BRAND IMAGE DAN BRAND ASSOCIATION TERHADAP PURCHASE INTENTION PENGGUNA MARKETPLACE WEDDINGKU DI INDONESIA - Muhammad Imaaduddin; Marcellia Susan; Ratih Tresnati (Journal of Global Business and Management Review, 2022)
This study aims to determine how Brand Image and Brand Association influence Purchase Intention. The method of research employed is quantitative research. As a sampling strategy for this study, a target sample of 300 individuals was chosen. The subjects of this study are Indonesian Weddingku Marketplace users. In this study, multiple regression analysis is employed as an analytical method. Analysis of the data indicates that Brand Image and Brand Association have a substantial impact on Purchase Intention. This research provides positive information to Marketplace Weddingku and other companies seeking information on the influence of Brand Image and Brand Association variables on Purchase Intention, as well as recommendations for company leaders in the formulation of future policies based on the research's conclusions and suggestions.